2021
DOI: 10.7759/cureus.19270
|View full text |Cite
|
Sign up to set email alerts
|

Natural Killer Cell Deficiency in Neuroblastoma Amplified Sequence Gene Mutation

Abstract: Natural killer cell deficiency (NKD) occurs when decreased levels of such cells lead to major immunological deficiency in the patient. NK cells participate in tumor cell surveillance, viral infections, and immunoregulation in the body. We report a case of a nine-year-old female child, a known case of neuroblastoma amplified sequence (NBAS) gene mutation in the variant c.2819A>C (p. His940Pro), which causes infantile liver failure syndrome type 2 (ILFS2). The patient had been treated at four years of age for a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…2). From this, we deduced that the NBAS C448R mutation might be associated with cytotoxic T-cell function, although a few studies reported that NBAS affected NK cells 20,22,23 . In addition, during the determination of autoantibodies related to hepatitis, anti-AMA-M2 and anti-M2-3E antibodies were found in the patient's serum (Supplementary Table S1).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…2). From this, we deduced that the NBAS C448R mutation might be associated with cytotoxic T-cell function, although a few studies reported that NBAS affected NK cells 20,22,23 . In addition, during the determination of autoantibodies related to hepatitis, anti-AMA-M2 and anti-M2-3E antibodies were found in the patient's serum (Supplementary Table S1).…”
Section: Discussionmentioning
confidence: 98%
“…NBAS is believed to be the second most frequently mutated gene in human hemophagocytic lymphohistiocytosis 21 , which is a life-threatening disease characterized by unbridled activation of cytotoxic T lymphocytes resulting in hypercytokinemia and immune-mediated injury of multiple organ systems. Mutations in the NBAS gene have previously been linked to immunologic aspects [21][22][23] , with general symptoms including decreased immunoglobulin G levels, CD56 + NK, and CD19 + naive B cells 22,24 . Our patient, who exhibited no decrease in CD19 B cells in peripheral blood (Supplementary Table S2), displayed normal IgG levels as in another study 20 ; however, our result supported that cytotoxic T cells (CD45 + CD8 + T cells) in the patient were higher than those in normal control children (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…We also found that the NBAS C448R mutation could be linked to immunode ciencies. Mutations in the NBAS gene have previously been linked to immunode ciencies, 21,22 with general symptoms of NBASlinked immunode ciencies including decreased immunoglobulin G levels, CD56 + NK, and CD19 + naive B cells. 21,23 However, our patient displayed normal IgG levels in another study, 20 and we believe that NBAS dysfunction also changed T cell homeostasis (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…We also supported that this NBAS C448R mutation could be linked to immunode ciencies. The mutations in NBAS gene has been linked to immunode ciencies in several literatures [19,20]. The general symptoms of NBAS-linked immunode ciencies were shown to be decreased immunoglobulin G levels, CD56 + NK and CD19 + naive B cells [19,21].…”
Section: Discussionmentioning
confidence: 99%